Metode Konsolidasi Tanah untuk Pengadaan Tanah yang Partisipasif dan Penataan Ruang yang Terpadu - Ida Nurlinda (Jurnal Hukum IUS QUIA IUSTUM, 2011)
Land acquisition for development especially development for public purpose is always a major problem in terms of the development of public interests. The issues are always centered on the location, compensation, and the definition of public interest itself. This research discusses land consolidation as a method of land acquisition which at the same time becomes the participative and integrated spatial planning instrument. Furthermore, it will discuss the legal aspects that may appear related to land consolidation as a land acquisition method and integrated and participative spatial planning instruments. The research result shows that land consolidation could become the method of participative land consolidation by involving private sector in providing utilities and infrastructure development in a consolidated area. Land consolidation does not only give economic advantages but also social and environmental advantages upon consolidated area.Key words : Land consolidation, land acquisition, spatial planning